ESTUDO MULTIDIMENSIONAL DE MULHERES PÓS-MENOPAUSA-INCONTINÊNCIA URINÁRIA: UM PROBLEMA DE SAÚDE PÚBLICA - Berlezi, Evelise M.; Bem, Andressa D.; Antonello, Carolina; Leite, Marinês T.; Bertolo, Elvio M. (Salão do Conhecimento, 2013)
Resumo